53.6k views
0 votes
Plz help me with it

Plz help me with it-example-1
User Felix C
by
4.9k points

2 Answers

4 votes

5 should be the answer I hope

User Tdebroc
by
5.2k points
7 votes

Answer: 5

Explanation:


√(4x+5)-√(x-1)=√(x+4)\\\\(√(4x+5)-√(x-1))^2=(√(x+4))^2\\\\4x+5-2√((4x+5)(x-1))+x-1=x+4\\\\5x+4-2√((4x+5)(x-1))=x+4\\\\4x=2√((4x+5)(x-1))\\\\2x=√((4x+5)(x-1))\\\\(2x)^2=(√((4x+5)(x-1)))^2\\\\4x^2=(4x+5)(x-1)\\\\4x^2=4x^2+x-5\\\\0=x-5\\\\5=x\\\\\\Check:\\√(4(5)+5)-√((5)-1)=√((5)+4)\\\\√(25)-√(4)=\sqrt9\\\\5-2=3\ \checkmark

User Plasmer
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.